2020
DOI: 10.1002/tpg2.20035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic gains with rapid‐cycle genomic selection for combined drought and waterlogging tolerance in tropical maize (Zea mays L.)

Abstract: Rapid cycle genomic selection (RC-GS) helps to shorten the breeding cycle and reduce the costs of phenotyping, thereby increasing genetic gains in terms of both cost and time. We implemented RC-GS on two multi-parent yellow synthetic (MYS) populations constituted by intermating ten elite lines involved in each population, including four each of drought and waterlogging tolerant donors and two commercial lines, with proven commercial value. Cycle 1 (C 1) was constituted based on phenotypic selection and interma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Genomic selection was applied to predict genetic value by combining genome-wide marker and phenotyping data of a training population to obtain genomic estimated breeding value (GEBV) [ 158 ]. In maize, rapid-cycle genomic selection (RCGS) for waterlogging tolerance in two multi-parent yellow synthetic populations showed a genetic gain of 38–113 kg ha −1 year −1 under waterlogging stress [ 159 ]. The results suggested that RCGS is an effective approach to breed varieties with superior qualities by introgressing parents with traits of interest [ 160 ].…”
Section: Breeding For Waterlogging Tolerancementioning
confidence: 99%
“…Genomic selection was applied to predict genetic value by combining genome-wide marker and phenotyping data of a training population to obtain genomic estimated breeding value (GEBV) [ 158 ]. In maize, rapid-cycle genomic selection (RCGS) for waterlogging tolerance in two multi-parent yellow synthetic populations showed a genetic gain of 38–113 kg ha −1 year −1 under waterlogging stress [ 159 ]. The results suggested that RCGS is an effective approach to breed varieties with superior qualities by introgressing parents with traits of interest [ 160 ].…”
Section: Breeding For Waterlogging Tolerancementioning
confidence: 99%
“…Genomic selection will also likely increase gain per unit cost by reduced genotyping cost per data point and reduced number of lines to be phenotyped [ 4 , 13 ]. As a result, GS is being implemented widely in breeding programs to improve genetic gain and expedite cultivar development by reducing cycles of selection [ 1 , 14 ]. Prediction accuracy is estimated as a correlation between GEBV and the phenotypic value of a trait [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This increased the genetic gain as the time required for selection was reduced significantly as compared to that of the conventional breeding scheme, where it was three times higher with phenotypic selection. Similarly, Das et al (2020) reported a genetic gain of 0.110 and 0.135 t/ha/yr for grain yield under drought and 0.038 and 0.113 t/ha/yr under water logging in two maize populations, viz., Maize Yellow Synthetic 1 and Maize Yellow Synthetic 2, respectively, following rapid cycling genomic selection. Vivek et al (2017) compared the performances of second cycle selection through phenotypic and rapid cycle genomic selection and found 10–20% superiority using the latter.…”
Section: Gs: Implications In Crop Improvementmentioning
confidence: 89%